Relations between basic and football specific motor abilities among first league female football players - Mandic Jelaska, P.; Lovric, F.; Bjelanovic, L. (3rd International Scientific Conference: Exercise and quality of life. April 12/13th 2013, 2013)
The aim of this study was to determine relations between basic and football specific motor abilities among first league female football players. According to the goal of the research, a sample consisted of 70 Croatian first league female football players (21.7±1.3 yr) was used. Participants were measured in 11 basic motor abilities tests and a set of 7 tests for assessing football-specific motor abilities. Footballspecific motor abilities were defined by a set of seven tests that have been shown to describe a football game in the context of five existing latent dimensions: precision of target shooting with the ball, ball handling, speed of ball handling, force of a leg kick, and speed of curvilinear running. By use of canonical correlation analysis, insight into the intensity (CanR=0.96, p=0.00) and structure of relations between basic motor and football specific motor variables was given. Results clearly indicate strong connections between basic and football-specific motor abilities in female football players of high competitive level and point to the necessity of parallel basic and specific motor abilities development among elite female football players.